Text neck syndrome and its association with mobile phone usage among university academic staff. - Bhat, Ishfaq Bashir; Miaraj, Ahmad Ali S Al (Longdom Publishing, 2021)
Background: Nowadays, mobile phones are one of the most used electronic devices in the world, and there are utilised almost by everyone in various societies and settings. The term ‘’Text Neck’’ or text neck syndrome (TNS) is explained as an incorrect postural alignment of neck muscles while using mobile phones or any other electronic gadget while texting for long durations. Purpose: The aim of this study is to identify the prevalence of text neck syndrome associated with prolong mobile phone usage and maintaining of an incorrect posture among university academic staff in International Islamic University Malaysia (IIUM), Kuantan Campus. Methods: The selected type of study design was a cross-sectional study with convenience sampling, the sample size was 117 academic staff selected from different faculties at International Islamic University of Malaysia Kuantan Campus (IIUMK), Pahang Darul Makmur, Malaysia. Results: the number of academic staff who participated in this study were roughly even. The sample included 59 males (50.4%) and 58 females (49.6%) and the mean age of participants in this study was (SD=38.38±6.05) with majority of participants ages fall between 30 to 40 years old (63.2%). Also, the duration of usage of mobile phone for working purpose has a significant value (P<0.001). Furthermore, mobile phone usage and its relation to posture when using a mobile phone has a significant value (P=0.073). Moreover, the prevalence of neck pain has a significant value (P=0.002) and it was found that female participants of those with neck pain (55%) are more than males with neck pain (27.1%). Conclusion: the study demonstrated the prevalence (p=0.002) of neck pain among smartphone users of university academic staff in International Islamic University Malaysia. It also depicted the importance of posture while using the mobile phone device and explained the faulty posture that contributes to the development of text neck syndrome. This supports the requirements for public health awareness toward academic staff.